The impact of ten years of infant universal Varicella vaccination in Sicily, Italy (2003-2012) - Amodio, Emanuele; Tramuto, Fabio; Cracchiolo, Manuela; Sciuto, Valentina; De Donno, Antonella; Guido, Marcello; Rota, Maria Cristina; Gabutti, Giovanni; Vitale, Francesco (Human vaccines & immunotherapeutics, 2015)
Introduction Universal varicella vaccination in Sicily was introduced in infant population since 2003, with a rapidly increasing coverage. Aim of the present study was to analyze changes in the epidemiology of varicella since the introduction of universal vaccination. Methods The study was performed by analyzing Sicilian administrative/clinical data on varicella case notifications and hospitalizations from 2003 to 2012 (ICD-9-CM discharge diagnosis codes 052 and 052.×). MMR+V and V coverage were also calculated for each birth cohort. Moreover, blood samples drawn in 2013/2014 from general population stratified by age were tested for varicella antibodies. Results From 2003 to 2012, 15 433 varicella cases were notified with a decreasing temporal trend (1.1/1000 population in 2003 to 0.1/1000 in 2012) (P < 0.001). In the same period, a total of 1145 patients were hospitalized with a diagnosis of varicella, with a 6-fold reduced risk of hospitalization over time (from 4.8 to 0.8/100 000 population per year; P < 0.001). Varicella vaccination coverage rates increased from 40% (2001 birth cohort) to 85% (2010 birth cohort), and inversely correlated with both notification and hospitalization rates (P < 0.001). Finally, 80.0% of subjects enrolled in the seroepidemiological survey were positive for varicella and seroprevalence increased significantly with age in both sexes (P < 0.001). Discussion The results show the impact of infant universal varicella vaccination in Sicily. Noteworthy, notifications and hospitalizations for varicella have significantly decreased after the introduction of universal vaccination, confirming the effectiveness of the adopted strategy.